2015
DOI: 10.1007/s10549-015-3561-6
|View full text |Cite
|
Sign up to set email alerts
|

Identifying patterns of breast cancer care provided at high-volume hospitals: a classification and regression tree analysis

Abstract: There is a growing body of literature linking hospital volume to outcomes in breast cancer. However, the mechanism through which volume influences outcome is poorly understood. The purpose of this study was to examine the relationship between hospital volume of breast cancer cases and patterns of processes of care in a population-based cohort of Medicare patients. A previously described and validated algorithm was applied to Medicare claims for newly diagnosed breast cancer cases in 2003 to identify potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…1215 On review of New York State data from 1984 to 1989, Roohan et al 16 demonstrated that patients receiving treatment for breast cancer at high-volume hospitals (≥150 breast surgeries performed per year) had a significantly improved survival at 5 years when compared with patients treated at lower volume centers. The authors also reported that higher mortality was associated with lower case volumes (19% in moderate-volume hospitals = 51 to 150 breast surgeries per year; 30% in low-volume hospitals = 11 to 50 breast surgeries per year; 60% in very low-volume hospitals = ≤10 breast surgeries per year).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1215 On review of New York State data from 1984 to 1989, Roohan et al 16 demonstrated that patients receiving treatment for breast cancer at high-volume hospitals (≥150 breast surgeries performed per year) had a significantly improved survival at 5 years when compared with patients treated at lower volume centers. The authors also reported that higher mortality was associated with lower case volumes (19% in moderate-volume hospitals = 51 to 150 breast surgeries per year; 30% in low-volume hospitals = 11 to 50 breast surgeries per year; 60% in very low-volume hospitals = ≤10 breast surgeries per year).…”
Section: Discussionmentioning
confidence: 99%
“…20 Multiple studies have suggested that treatment at high-volume centers is associated with the receipt of evidence-based care, including multidisciplinary consultations, and more frequent use of breast conservation, adjuvant chemotherapy, and radiation. 6,13,15,19,20,21 Kong et al 15 demonstrated that use of sentinel lymph node biopsy was the aspect of care that most notably differed between high versus low-volume centers, and correlated with more frequent use of adjuvant therapy (including chemotherapy, radiation, and endocrine therapy) in their series. A similar phenomenon could explain the improved survival among hormone-receptor positive breast cancers seen in our study; favorable biology leaves a greater chance for cure, and decisions about systemic therapy in this population are nuanced and multifactorial.…”
Section: Discussionmentioning
confidence: 99%
“…In a comprehensive review of health services literature, hospital or physician volume or specialty has been found to affect outcome of cancer care [9]. Hospital volume has been associated with patterns of care reflecting the most current standards of care in patients with breast cancer [10]. High volume hospitals are associated with better outcomes also for different cancers types [1117].…”
Section: Discussionmentioning
confidence: 99%
“…Although better care has generally been observed among breast cancer patients treated by high-volume surgeons, none of the previously published studies have used the EUSOMA criteria to assess the quality of care received. As reported in previous studies, we found that surgeons who performed >10 operations/year more frequently performed a histological assessment before surgery [37,38], removed sentinel lymph nodes when indicated [39][40][41][42][43], removed an adequate number of axillary lymph nodes when performing axillary clearance [44,45], and referred their patients for adjuvant radiotherapy when indicated [5,45,46].…”
Section: What Was Already Known On the Topic?mentioning
confidence: 62%